Letter (copy) - Tewson, Vincent
1939-07-12 038-0089-002 - 2 - enable you and your wife to meet the convoy at the port of arrival in France. I am happy to be in a position to give you this information, and congratulate you on the prospect of your being reunited once more with your children. Yours sincerely, Assistant Secretary. 292/946/38/89(II)